2022
DOI: 10.1056/nejmoa2117128
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Covid-19 Vaccines over a 9-Month Period in North Carolina

Abstract: Background The duration of protection afforded by coronavirus disease 2019 (Covid-19) vaccines in the United States is unclear. Whether the increase in postvaccination infections during the summer of 2021 was caused by declining immunity over time, the emergence of the B.1.617.2 (delta) variant, or both is unknown. Methods We extracted data regarding Covid-19–related vaccination and outcomes during a 9-month period (December 11, 2020, to September 8, 2021) for approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
272
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(304 citation statements)
references
References 19 publications
27
272
2
3
Order By: Relevance
“…In addition, more than two-thirds of those admitted to ICUs received one injection of a COVID-19 vaccine (Oxford-AstraZeneca or Pfizer-BioNTech). These findings are in accordance with the published literature that reported the effectiveness of vaccines in reducing mortality and the importance of full immunization against COVID-19, which results in lower rates of hospitalization and mortality [47][48][49]. Even though there was no difference in the odds of mortality between the two vaccines (Oxford-AstraZeneca and Pfizer-BioNTech), each one of these vaccines resulted in significant reduction in the odds of mortality, as previously reported [30].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, more than two-thirds of those admitted to ICUs received one injection of a COVID-19 vaccine (Oxford-AstraZeneca or Pfizer-BioNTech). These findings are in accordance with the published literature that reported the effectiveness of vaccines in reducing mortality and the importance of full immunization against COVID-19, which results in lower rates of hospitalization and mortality [47][48][49]. Even though there was no difference in the odds of mortality between the two vaccines (Oxford-AstraZeneca and Pfizer-BioNTech), each one of these vaccines resulted in significant reduction in the odds of mortality, as previously reported [30].…”
Section: Discussionsupporting
confidence: 93%
“…Studies during mid-2021 reported VE of 79.8% 7 and 79.9-98.4% 4 against infection and 95.3% 7 , 86% (CI 82-88%) 5 , 80-97.5% 4 , and 80.0% (CI 76.8-82.7%) 9 against hospitalization across different variants. A recent study that looked further at the waning VE from late 2020 through Q3 of 2021 found VE rates for mRNA vaccines to be the highest two weeks after a two-dose vaccination regimen (94.5%; CI 94.1-94.9%), lining up with our estimates of VE in Q2, and lowest at 66.6% (CI 65.2-67.8%) after seven months 8 , which corresponds with our VE estimates in Q3. Taken together, these results highlight the need for appropriate adjustment for patient covariates, timing of vaccination, booster status, and for replication across different regions and time periods to more fully understand VE and potential VE modifying factors.…”
Section: Discussionsupporting
confidence: 67%
“…The drop of anti-Spike IgG levels is apparent as early as 70 days after the completion of a full vaccination scheme, with a two- and five-fold reduction compared with the levels at 20–40 days for BNT162b2 and ChAdOx1 recipients, respectively [ 36 ]. Given that there is a parallel trend regarding neutralizing antibody titers [ 35 ], which may serve as a surrogate of immunity against SARS-CoV-2 [ 37 ], this humoral phenomenon coincides with a gradually increasing susceptibility of fully vaccinated individuals for breakthrough infections in the months following immunization [ [38] , [39] , [40] , [41] ]. As immunity diminishes over time, the most notable decreases in vaccine effectiveness have occurred in milder forms and asymptomatic infections, in those vaccinated earliest, in older subjects and in those infected with the Omicron variant [ 15 , 23 ].…”
Section: What Are the Causes Of Breakthrough Infections?mentioning
confidence: 99%